Firefighter and fire instructor's physiological responses and safety in various training fire environments. (July 2019) - Horn, Gavin P.; Stewart, Jacob W.; Kesler, Richard M.; DeBlois, Jacob P.; Kerber, Steve; Fent, Kenneth W.; Scott, William S.; Fernhall, Bo; Smith, Denise L.
Highlights: Vastly different training environments resulted in similar physiological responses. Instructors' hemostatic response were significantly blunted versus firefighters. Work-rest cycles should be based on activity not environment when working in gear. Abstract: For firefighters around the world, fire training is necessary to ensure operational readiness, but can be hazardous. Fire instructors routinely attempt to design safe but realistic scenarios and may do so in very different thermal environments. Yet, the physiological burden (and presumed physiological benefits) of different training has rarely been investigated. We studied the impact of three training fire environments: (a) pallets (Pallet), (b) oriented strand board (OSB) and simulated fire/smoke (Fog) on firefighters' and fire instructors' physiological responses. Peak ambient temperatures exceeded 420 °C in Pallet and OSB scenarios, but were less than 40 °C for Fog. Firefighters' peak core temperatures, heart rates and hemostatic responses were not statistically different among the training environments despite the large differences in ambient conditions. Instructors' heart rate and hemostatic responses were significantly blunted compared to the firefighters' despite similar peak core temperatures, suggesting instructors performed less work or were less stressed. It is important that physiological responses experienced by firefighters and instructors working in fully encapsulating personal protective equipment be considered based on intensity and duration of work, regardless of the apparent risk from ambient conditions.